Strain Sensors: Porous Fibers Composed of Polymer Nanoball Decorated Graphene for Wearable and Highly Sensitive Strain Sensors (Adv. Funct. Mater. 45/2019). (6th November 2019) - Huang, Tao; He, Peng; Wang, Ranran; Yang, Siwei; Sun, Jing; Xie, Xiaoming; Ding, Guqiao
Abstract : In article number 1903732, Peng He, Guqiao Ding, and co‐workers prepare a porous composite fiber composed of graphene networks and decorated polymer nanoballs for wearable strain sensors. With an optimized graphene‐polymer interface area, these fibers show excellent sensitivity, a low detection limit, and long durability to small strains, which enables weaving into fabrics for motion and location detection.